2019
DOI: 10.1016/j.bpj.2019.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Hinge Flexibility in the APP Transmembrane Domain Alters γ-Secretase Cleavage

Abstract: Intramembrane cleavage of the b-amyloid precursor protein C99 substrate by g-secretase is implicated in Alzheimer's disease pathogenesis. Biophysical data have suggested that the N-terminal part of the C99 transmembrane domain (TMD) is separated from the C-terminal cleavage domain by a di-glycine hinge. Because the flexibility of this hinge might be critical for g-secretase cleavage, we mutated one of the glycine residues, G38, to a helix-stabilizing leucine and to a helix-distorting proline. Both mutants impa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 116 publications
5
50
0
Order By: Relevance
“…Since the destabilizing function of glycine results from a packing defect due to its missing side chain ( Högel et al, 2018 ), we reasoned that the small side chain of both neighboring alanine residues might also contribute to local helix flexibility. This compares to the sequence context of the G37G38 hinge of the C99 TM helix, where the GG motif is flanked by insufficiently packing VAL residues V36, V39, V40 ( Götz et al., 2019b ; Hitzenberger et al., 2020 ). Consequently, we replaced the A 42 G 43 A 44 motif by leucine residues (TNFα AGA/LLL).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the destabilizing function of glycine results from a packing defect due to its missing side chain ( Högel et al, 2018 ), we reasoned that the small side chain of both neighboring alanine residues might also contribute to local helix flexibility. This compares to the sequence context of the G37G38 hinge of the C99 TM helix, where the GG motif is flanked by insufficiently packing VAL residues V36, V39, V40 ( Götz et al., 2019b ; Hitzenberger et al., 2020 ). Consequently, we replaced the A 42 G 43 A 44 motif by leucine residues (TNFα AGA/LLL).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies suggested that intramembrane proteolysis by GxGD-aspartyl proteases is affected by the conformational flexibility of a substrate's TM helix ( Fluhrer et al., 2012 ; Götz et al., 2019b ; Langosch et al., 2015 ; Langosch and Steiner, 2017 ). To elucidate whether similar determinants also influence SPPL2a-mediated non-canonical shedding of TNFα, all serines (S34, S37), glycines (G43), cysteine (C49), and histidines (H52) in the TNFα TM domain were substituted by alanine, leucine, or proline.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, both experimental and computational studies have shown that the TMD of C99 is flexible (45,(102)(103)(104)(105)(106)(107). At the same time, C99 has been shown to be adaptable to changes in bilayer thickness, wherein the Cterminus of its TMD has a fixed transmembraneend site (defined by three consecutive lysine residues) but the N-terminus of the TMD helix seems to be energetically tolerant of being either membrane-buried (in thicker bilayers) or water exposed (in thinner bilayers) (108).…”
Section: Discussionmentioning
confidence: 99%